Effects of cash transfers on household resilience to climate shocks in the arid and semi arid counties of northern Kenya. Issue 1 (31st December 2023) - Matata, Michael Joseph; Ngigi, Margaret W.; Bett, Hillary Kiplangat
ABSTRACT: Climatic events and other natural-related disasters experienced in the arid and semi-arid lands of northern Kenya negatively affect the pastoral livelihoods of the communities. Addressing vulnerability to climate shocks among pastoral communities of Kenya's Arid and Semi-lands presents a persistent challenge. Cash transfer programmes have increasingly grown as one mode of building household resilience. Understanding the role of cash transfer interventions on household resilience to climate shocks is key to policy programming. This paper aimed at determining the effects of cash transfers on household resilience to climate shocks. The paper evaluated the Hunger Safety Net Program, which is one of the largest unconditional cash transfer programs in Kenya. The Hunger Safety Net Program targeted poor people in northern Kenya including the counties of Turkana, Wajir, Marsabit, and Mandera. To establish the impact the paper compares households which received cash transfers with those that did not receive transfers. The panel fixed effects model was used to determine the effects of cash transfers on household resilience. The results indicate that cash transfers have positive significant effects on household resilience to climate shocks.